Approximate Symmetry Analysis and Approximate Conservation Laws of Perturbed KdV Equation - Yu-Shan Bai; Qi Zhang (Advances in Mathematical Physics)
Approximate symmetries, which are admitted by the perturbed KdV equation, are obtained. The optimal system of one-dimensional subalgebra of symmetry algebra is obtained. The approximate invariants of the presented approximate symmetries and some new approximately invariant solutions to the equation are constructed. Moreover, the conservation laws have been constructed by using partial Lagrangian method.